2020
DOI: 10.5114/ada.2020.96260
|View full text |Cite
|
Sign up to set email alerts
|

The ambiguous pruritogenic role of interleukin-31 in cutaneous T-cell lymphomas in comparison to atopic dermatitis: a review

Abstract: Cutaneous T-cell lymphomas (CTCLs) comprise a group of chronic heterogeneous diseases of unknown pathogenesis, characterized by non-specific skin lesions such as patches, plaques and tumours. CTCL is accompanied by persistent pruritus poorly responding to antihistamines and therefore significantly reducing quality of life in patients with lymphomas. According to research data, interleukin-31 (IL-31) contributes to initiation and maintenance of the inflammatory process of the skin and pruritus in inflammatory d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…It has been hypothesized that IL-31 may induce epidermal neoplastic T cells and keratinocytes to transmit itch, indirectly affecting sensory nerves (54). Although IL-31 appears to have a role in pruritus in CTCL, there is conflicting evidence as to whether it plays a larger role in the pathogenesis of CTCL itself (56,58,59). However, of note, chronic prurigo has also been reported in cases of Hodgkin lymphoma (HL) (60), and a study in HL patients demonstrated elevated IL-31 in HL cells and in the immune cells infiltrating affected lymph nodes (61).…”
Section: Cutaneous T-cell Lymphoma (Ctcl)mentioning
confidence: 99%
“…It has been hypothesized that IL-31 may induce epidermal neoplastic T cells and keratinocytes to transmit itch, indirectly affecting sensory nerves (54). Although IL-31 appears to have a role in pruritus in CTCL, there is conflicting evidence as to whether it plays a larger role in the pathogenesis of CTCL itself (56,58,59). However, of note, chronic prurigo has also been reported in cases of Hodgkin lymphoma (HL) (60), and a study in HL patients demonstrated elevated IL-31 in HL cells and in the immune cells infiltrating affected lymph nodes (61).…”
Section: Cutaneous T-cell Lymphoma (Ctcl)mentioning
confidence: 99%
“…The most studied model was CTCL, where the pathogenetic mechanism seems to be emblematic. The researches collected together with other reports were not able to clarify if interleukin 31 is connected to the itch, to the cancer or to both [ 42 ]. These data are encouraging in respect to a potential anti-pruritic treatment based on reducing IL-31 or its receptor IL-31RA.…”
Section: Discussionmentioning
confidence: 99%
“…82,83 As a major product of CD4 + T cells in DOCK8 deficient mice, IL-31 appears to be involved in the DOCK8 mutation-driven hyper IgE syndrome, characterized by a combined immunodeficiency, eczematous skin lesion, and high serum IgE levels. 84 Finally, initial, yet mostly descriptive or non-controlled and small scale human studies/trials suggest an involvement of IL-31 in various cutaneous disorders beyond AD including pemphigus herpetiformis, 85 chronic spontaneous urticaria, 86,87 cutaneous T-cell lymphoma, [88][89][90][91][92] systemic lupus erythematosus, 93,94 bullous pemphigoid, [95][96][97] dermatomyositis, 98 and psoriasis. 70,[99][100][101][102] This needs to be further explored, especially given the potential beneficial effect of new anti-IL-31 strategies in these sometimes hard-to-treat skin diseases.…”
Section: The Il-31 Axis In the Skinmentioning
confidence: 99%
“…Finally, initial, yet mostly descriptive or non‐controlled and small scale human studies/trials suggest an involvement of IL‐31 in various cutaneous disorders beyond AD including pemphigus herpetiformis, 85 chronic spontaneous urticaria, 86,87 cutaneous T‐cell lymphoma, 88–92 systemic lupus erythematosus, 93,94 bullous pemphigoid, 95–97 dermatomyositis, 98 and psoriasis 70,99–102 . This needs to be further explored, especially given the potential beneficial effect of new anti‐IL‐31 strategies in these sometimes hard‐to‐treat skin diseases.…”
Section: Introductionmentioning
confidence: 99%